Synchronization Control of Complex Dynamical Networks Based on Uncertain Coupling - Qianqian Jia (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexIn recent years, the study of complex networks has been a focus subject of technology fields. In this paper, we consider the adaptive control and synchronization of uncertain complex networks. By using the adaptive control techniques with the linear feedback updated law and the well-known LaSalle invariant principle on dynamical system theory, some simple yet generic criteria are derived. Furthermore, the result is applied to typical chaotic cellular neural networks (CNN). Finally, numerical simulations are presented to demonstrate the feasibility and effectiveness of the proposed techniques.